Pengaruh Integritas, Independensi, dan Profesionalisme terhadap Kualitas Audit pada Inspektorat Sumatera Barat - Yundari, Dini; Syofyan, Efrizal (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to examine how much influence integrity,  independence, and professionalism have on audit quality at the inspectorate of West Sumatera Province. This study uses a casual associative quantitative approach. The population  in this study were all auditors who worked at the West Sumattera Provincial Inspectorate office, totaling 40  people. The sample selection technique used a saturated sample. This research instrument uses a questionnaire. The data analysis technique of this research is multiple linear regression aanalysis.The results showed that together there was a significant influence between Integrity Independence, and Professionalism on Audit Qualilty at the Inspectorate of West Sumatera Province. Integrity has a positive and significant effect on Audit Quality, Independence has no positive and significant effect on Audit Quality, and Professionalism also has no positive and significat affect on Audit Quality. This study consludes that improving audit quality requires increasing integrity.